(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This study explores contemporary trends in housing design and construction within the historic core of Samarkand, Uzbekistan, with comparative insights from Turkey and Europe. The introduction highlights the tension between urban modernization and heritage preservation in rapidly transforming historic cities. While Samarkand faces increasing pressure from tourism-driven development, its architectural identity rooted in traditional mahalla structures is at risk. The research identifies a critical knowledge gap in how modern housing projects in Central Asian historic cities integrate—or fail to integrate—traditional architectural and cultural values. Methodologically, the study employs qualitative analysis of urban policy documents, architectural case studies (e.g., Kosh-Khauz project), and comparative literature on heritage conservation practices. Findings reveal divergent approaches: Samarkand exhibits both sensitive adaptive reuse and disruptive redevelopment, with limited community engagement and inconsistent enforcement of heritage protection laws. In contrast, Turkey demonstrates stronger adaptive reuse models, though not without failures, while European cities apply strict zoning and incentivize preservation. The results suggest that urban heritage management in Samarkand lacks coherent integration between policy, community, and design practice. The study implies that adopting more participatory and legally grounded conservation frameworks—similar to those in Europe—could help balance modernization with the safeguarding of local identity. These findings contribute to the global discourse on sustainable heritage-led urban development.